Attantività – Per una fenomenologia performativa dei corpi scenici (Muse, 2025)
The essay investigates the ontological reciprocity between the one who sees and the one who is seen, approaching vision not as a unilateral act but as an embodied relation between human and non-human bodies, active and resistant. Starting from the concept of actantivity, the contribution explores seeing as a performative event in which matter participates, acts, and reveals itself as vital. The mirror, the image, and the stage become dispositifs of crisis, sites where the subject recognizes itself as object and vice versa, opening a phenomenological paradox that destabilizes any narcissistic conception of vision. Through references to Merleau-Ponty, Spinoza, Latour, Bennett, and Haraway, and the analysis of artistic practices ranging from Parmigianino to Cunningham, Forsythe, and De Keersmaeker, the reflection focuses on theatre as an ontological laboratory: a space of concatenations in which different actants, each with an irreducible singularity, cooperate in the production of the event. The contemporary stage thus appears as a relational, unrepeatable, and unstable event, where responsibility does not coincide with the action of the individual but emerges from the fabric of interactions. Actantivity therefore takes shape as a theoretical key for understanding the ontological vitality of scenic bodies and, more broadly, as a post-human paradigm of relation. From this perspective, theatre does not represent reality but exposes it in its power of shared existence, bringing forth an ontology of flesh and co-presence, where to see always also means to be seen.
Keywords: Attantività; Fenomenologia; Ontologia; Teatro; Coreografia